Paint composition
The coating composition, featuring a rubber base resin, dispersed oil, and fluororesin particles, addresses the challenge of providing long-term excellent release properties on heat-sensitive substrates, ensuring durable and moldable coatings.
Patent Information
- Application Number
- JP2021036511
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-08
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2041-03-08
AI Technical Summary
Existing coating compositions fail to provide long-term excellent release properties on substrates with poor heat resistance, such as rubber and plastic, and do not adequately follow the elasticity of these substrates.
A coating composition is developed that includes a rubber base resin, dispersed oil with an average particle size of 50 μm or less, and fluororesin particles, which together form a durable coating film with improved adhesion and followability on elastic substrates.
The coating composition achieves excellent durability and non-adhesion (release property) over a long period, even on substrates with poor heat resistance, while maintaining excellent moldability and productivity.
Smart Images

Figure 0007659409000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating composition, and more specifically, to a coating composition that can be applied to substrates having poor heat resistance, such as rubber or plastic, and that can form a coating film having excellent durability and capable of maintaining its non-stickiness (mold releasability) for a long period of time. [Background technology]
[0002] Molds for molding polymeric materials such as plastic materials and rubber materials, ceramics, cement, etc. require mold releasability on the mold surface in order to remove the molded product without defects. As a coating composition capable of forming a coating film for improving the mold releasability of such mold surfaces, the present inventors have proposed a coating composition containing a fluororesin and a specific oil (Patent Documents 1 and 2). Molds having a coating film made of such a coating composition on their surface also have excellent durability that allows them to exhibit excellent mold releasability for a long period of time, but are not suitable for coating resin substrates that cannot withstand heat treatment for coating formation, or substrates having elasticity such as rubber.
[0003] On the other hand, even for resin substrates and rubber substrates, there is a demand for coating compositions that can impart releasability that can withstand long-term use. For example, when molding tires, a member mainly made of rubber called a bladder is generally used to press the rubber composition that will become the tire from the inside of the mold, and there is a demand for coatings that can form a coating film with high durability and high releasability on the surface of this bladder. In addition, when molding rubber shoe soles (rubber soles), it is common to use a resin mold for injection molding so that design changes can be easily accommodated, and when removing a rubber molded product from the resin mold, the resin mold also requires releasability.
[0004] Patent Document 3 listed below describes a non-adhesive composition that can be used as an anti-blocking agent for synthetic resins and vulcanized or unvulcanized rubber, which contains (A) a compound having a perfluoroalkyl or alkenyl group having 4 to 20 carbon atoms, (B) polytetrafluoroethylene having a number average molecular weight of 500,000 or less, and (C) at least one compound selected from the group consisting of silicone oil, silicone resin, and highly fluorinated compounds (excluding those contained in components (A) and (B)) having a boiling point of 100°C or higher, represented by the general formula: CF2CFCln (wherein n = 2 to 15), etc.
[0005] Furthermore, as a method for improving the releasability (lubricity) of the surface of a bladder used in tire molding, the following Patent Document 4 describes coating the outer surface of the bladder with a release agent composition in the form of an oil-in-water emulsion containing a reactive polyorganosiloxane, a crosslinking agent, a non-reactive linear polyorganosiloxane oil, glass beads, a surfactant, an additive, and the like. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2018-90772 A [Patent Document 2] JP 2019-203087 A [Patent Document 3] Patent No. 3348433 [Patent Document 4] Patent No. 6255604 Summary of the Invention [Problem to be solved by the invention]
[0007] The composition described in Patent Document 3 is used as an antiblocking agent for synthetic resins and vulcanized or unvulcanized rubbers, but there is a risk that durability sufficient to exhibit excellent releasability over a long period of time may not be obtained in products that are repeatedly stretched and contracted, such as bladders. In addition, the release agent composition described in the above Patent Document 4 is intended to increase the number of demolding operations possible by application, i.e., to improve durability, but in the specific embodiment, which is an Example, the number of demolding operations is a maximum of 18, which is not sufficient. In addition, in order to increase the number of demolding operations, glass beads with an average particle diameter of up to 150 μm are blended, but when the composition is applied to a resin mold used for injection molding, the unevenness caused by the glass beads is transferred to the surface of the molded product, and there is a risk that a smooth surface cannot be obtained.
[0008] Therefore, an object of the present invention is to provide a coating composition capable of forming a coating film that exhibits excellent releasability for a long period of time on a substrate having poor heat resistance, such as a rubber or plastic substrate, without causing the problems described above. Another object of the present invention is to provide a coating composition capable of forming a coating film capable of conforming to elastic substrates such as rubber bladders used in tire manufacturing, and a rubber or plastic substrate having this coating film. [Means for solving the problem]
[0009] According to the present invention, rubber and oil that is liquid at 25° C. And fluororesin particles Including, The rubber is contained in an amount of 50% or more of the total base resin, The oil is dispersed in a coating composition having an average particle size of 50 μm or less. In the coating composition of the present invention, 、 ( 1 ) containing a silane coupling agent; ( 2 ) the oil is contained in an amount of 1 to 35% by weight of the amount (solid content) of the rubber in the coating composition or the total amount (solid content) of the rubber and the fluororesin particles; ( 3 ) the rubber is contained in an amount of 40% by weight or more of the total amount (solid content) of the rubber and the fluororesin particles in the coating composition; ( 4 ) the rubber is hydrogenated acrylonitrile butadiene rubber or silicone rubber; (5 ) the oil is a fluorine oil or a silicone oil; ( 6 ) the fluororesin particles are made of a melt processable fluororesin; ( 7 ) the fluororesin particles are made of PFA or FEP; is preferred.
[0010] The present invention also provides a rubber or plastic substrate having a coating film formed on its surface from the above coating composition. In the rubber or plastic substrate of the present invention, it is preferable that the coating film has an n-hexadecane contact angle of 50 degrees or more. Effect of the Invention
[0011] The coating composition of the present invention can form a coating film having excellent durability and excellent non-adhesiveness (releasability) for a long period of time on not only heat-resistant substrates such as aluminum substrates, but also substrates with poor heat resistance such as substrates made of rubber or plastic. Also, a coating film having excellent conformability can be formed on elastic substrates such as rubber substrates. Furthermore, since the oil is dispersed in the paint composition with an average particle size of 50 μm or less, and is also dispersed inside the coating film that is formed, even if the coating film wears down with use, the oil inside the coating film gradually seeps out to the surface, making it possible for the coating to exhibit high non-stick properties (release properties) over the long term. Furthermore, rubber substrates and plastic substrates such as bladders and resin molds having a coating film made of the coating composition of the present invention have excellent moldability due to their excellent releasability, and since this releasability is maintained for a long period of time, they also have excellent productivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (Paint composition) An important feature of the coating composition of the present invention is that it contains rubber and an oil that is liquid at 25° C., and that the oil is dispersed with an average particle size of 50 μm or less. In the coating composition of the present invention, oil that is in a fluid state at 25°C (room temperature) seeps out onto the surface of the coating film that is formed, imparting release properties to the substrate. By using rubber as the base resin of the coating composition, the coating film that is formed has excellent adhesion to rubber and plastic substrates, and because the coating film can follow the expansion and contraction of the rubber substrate, the occurrence of cracks is effectively prevented, making it possible to impart excellent release properties to rubber substrates for a long period of time. In the present invention, the rubber that serves as the base resin is used in an unvulcanized state and is vulcanized when the coating film is formed. Since the vulcanization temperature can be kept below 200°C (preferably below 180°C), the coating composition of the present invention can be used without problem on plastic or rubber substrates that can be used at temperatures above that temperature.
[0013] In the coating composition of the present invention, the oil is contained, and the oil seeps out onto the coating surface, improving the non-adhesiveness (releasability) of the coating. Furthermore, the oil reduces friction, reduces the coefficient of friction of the coating (improves slipperiness), and improves the abrasion resistance of the coating. Furthermore, in the present invention, the oil is present in the coating composition in a dispersed state with an average particle size of 50 μm or less, so that the oil is also present inside the coating film that is formed. Therefore, even if the coating film is worn down due to use, the oil inside the coating film gradually seeps out to the surface, making it possible to exhibit high non-adhesiveness (releasability) for a long period of time. The average particle size of the dispersed particles of the oil in the coating composition is 50 μm or less, preferably 20 μm or less, more preferably 10 μm or less, and particularly preferably 5 μm or less. The measurement of the average particle size will be described later.
[0014] As described above, the coating composition of the present invention may be in the form of a water-based coating composition, a solvent-based coating composition or a powder coating composition so long as it contains a combination of rubber and oil. From the viewpoints of environment and cost, however, it is preferable that it is a water-based coating composition.
[0015] [Rubber] The rubber used as the base resin in the coating composition of the present invention may be either natural rubber or synthetic rubber. Specific examples of synthetic rubbers include conventionally known synthetic rubbers such as silicone rubber, acrylic rubber, isoprene rubber (IR), urethane rubber, ethylene vinyl acetate rubber (EVA), epichlorohydrin rubber, ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), chlorosulfonated polyethylene (CSM), styrene butadiene rubber (SBR), thiokol, butyl rubber (IIR), butadiene rubber (BR), acrylonitrile butadiene rubber (NBR), ethylene propylene rubber (EPR), and fluororubber. In the present invention, hydrogenated acrylonitrile butadiene rubber (HNBR) and silicone rubber can be preferably used from the viewpoints of having heat resistance, durability after vulcanization, adhesion to the substrate or releasability, and being able to maintain an elongation rate of 50% or more even after forming a coating film.
[0016] The hydrogenated acrylonitrile butadiene rubber (HNBR) may be either partially hydrogenated or fully hydrogenated, and preferably has an acrylonitrile content in the range of 10 to 50% by weight. Also, the Mooney viscosity ML(1+4) (based on JIS K6300) at 100°C is preferably in the range of 30 to 150. As the silicone rubber, any conventionally known silicone rubber can be used, and preferred examples include, but are not limited to, methyl silicone rubber, vinyl methyl silicone rubber, and phenyl methyl silicone rubber.
[0017] The adhesion of the coating film can be further improved by using the same type of rubber component in the coating composition as that of the substrate to which the coating composition is applied. That is, for substrates made of silicone rubber, it is preferable to use silicone rubber as the rubber in the coating composition, and for substrates made of hydrocarbon rubbers such as butyl rubber (IIR) and acrylonitrile butadiene rubber (NBR), it is preferable to use hydrogenated acrylonitrile butadiene rubber (HNBR).
[0018] In the coating composition of the present invention, the rubber serving as the base resin is preferably contained in the coating composition in an amount of 10 to 50% by weight in terms of solid content. Even when fluororesin particles are contained, it is preferable that 40% or more, especially 50% or more of the entire base resin (total amount of solids of rubber and fluororesin particles) is made of rubber. This enables the formation of a coating film at the above-mentioned low temperature and allows the formation of a coating film with excellent non-stickiness (mold releasability) and good adhesion without deteriorating plastic or rubber substrates.
[0019] [oil] The oil that is liquid at 25°C used in the coating composition of the present invention is one that exhibits fluidity at room temperature (25°C), and various oils can be used as long as this condition is met, but as described above, the purpose of the oil is to exude onto the surface of the coating film that is formed and improve the non-adhesiveness (mold releasability) of the coating film, so it is preferable that the surface tension of the oil itself is small. That is, the surface tension of the oil at 25°C is preferably 30mN / m or less, and more preferably 20mN / m or less. In addition, it is preferable that the oil has heat resistance that can withstand heating during crosslinking of rubber and does not volatilize when heated, and it is preferable that the decomposition (volatilization) temperature is 200°C or more. In order to satisfy these conditions, it is necessary that the oil has excellent heat resistance and small intermolecular interaction. Examples of such oils include fluorine oils, silicone oils, modified silicone oils, and hydrocarbon oils such as alkanes having 15 to 100 carbon atoms, higher fatty acids having 5 to 50 carbon atoms, fatty acid esters, polyol esters, polyglycols, polyethers, and polyphenyl ethers, and these oils can be used alone or in combination, but in the present invention, fluorine oils or silicone oils can be used preferably.
[0020] Examples of fluorinated oils include, but are not limited to, perfluoropolyethers (PFPEs), perfluoroalkyl polyethers, telomers of fluorinated monomers (e.g., tetrafluoroethylene (TFE), trifluoroethylene, vinylidene fluoride, chlorotetrafluoroethylene (CTFE), fluorinated acrylic monomers, etc.), and other specific fluorinated hydrocarbon compounds. In the present invention, PFPE can be suitably used, which has a small surface energy and can efficiently improve the non-adhesive properties (release properties) of the coating film, and is available under the trade names Krytox (registered trademark) (manufactured by Chemours Inc.) and Demnum (registered trademark) (manufactured by Daikin Corporation).
[0021] Examples of silicone oils include, but are not limited to, straight silicone oils such as dimethyl silicone oil, methylphenyl silicone oil, and methylhydrogen silicone oil, monoamine-modified silicone oil, diamine-modified silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, alicyclic epoxy-modified silicone oil, carbinol-modified silicone oil, mercapto-modified silicone oil, carboxyl-modified silicone oil, hydrogen-modified silicone oil, reactive modified silicone oils such as amino-polyether-modified silicone oil, epoxy-polyether-modified silicone oil, and epoxy-aralkyl-modified silicone oil, polyether-modified silicone oil, aralkyl-modified silicone oil, fluoroalkyl-modified silicone oil, halogen-modified silicone oil, long-chain alkyl-modified silicone oil, higher fatty acid ester-modified silicone oil, higher fatty acid amide-modified silicone oil, polyether-long-chain alkyl-aralkyl-modified silicone oil, and non-reactive modified silicone oils such as long-chain alkyl-aralkyl-modified silicone oil. Among these, methylphenyl silicone oil, which can be used in food applications, can be preferably used.
[0022] The oil is preferably contained in an amount of 1 to 35% by weight, more preferably 2 to 20% by weight, and more preferably 5 to 10% by weight, based on the solid content of the base resin in the coating composition (rubber, or the total of rubber and fluororesin particles when fluororesin particles are contained). If the amount of oil is less than the above range, the non-adhesiveness (mold releasability) of the coating film may not be sufficiently improved compared to when it is within the above range, while if the amount of oil is more than the above range, coating film formation may become more difficult than when it is within the above range, causing coating defects and impairing abrasion resistance.
[0023] [Fluororesin particles] In the coating composition of the present invention, it is preferable to further contain fluororesin particles. That is, by containing fluororesin particles, the surface energy of the coating film is reduced, the slipperiness is improved, and the non-adhesiveness (releasability) of the coating film is improved. In addition, since the abrasion resistance is improved by reducing the friction coefficient, the non-adhesiveness (releasability) is maintained for a long period of time, and the durability is also improved. Furthermore, as described below, by baking the coating at a temperature of around 180°C, the fluororesin particles do not melt in the coating, and instead form a sea-island structure in which the fluororesin particles are islands in a rubber matrix (sea), so the elasticity of the rubber coating is not impaired. Examples of such fluororesin particles that can be used include, but are not limited to, fluororesin particles made of polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-hexafluoropropylene-perfluoro(alkyl vinyl ether) copolymer, tetrafluoroethylene-ethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, chlorotrifluoroethylene-ethylene copolymer, and the like.
[0024] Of the above-mentioned fluororesin particles, it is preferable to use a heat-meltable fluororesin, and from the viewpoint of the non-stickiness and heat resistance of the coating film, heat-meltable perfluororesins such as low molecular weight PTFE, PFA, FEP, and tetrafluoroethylene-hexafluoropropylene-perfluoro(alkyl vinyl ether) copolymers are preferably used, with PFA and FEP being particularly preferred. The alkyl group of the perfluoro(alkyl vinyl ether) in the PFA preferably has 1 to 5 carbon atoms, and among these, perfluoro(propyl vinyl ether) (PPVE), perfluoro(ethyl vinyl ether) (PEVE), and perfluoro(methyl vinyl ether) (PMVE) are particularly suitable. The amount of the perfluoro(alkyl vinyl ether) in the PFA is preferably in the range of 1 to 50% by weight.
[0025] The fluororesin particles can be used as fluororesin powder particles, but since excellent releasability can be obtained by finely dispersing the fluororesin particles in the coating film, it is preferable to mix the dispersion obtained by emulsion polymerization as a raw material for the coating material. The average particle size of the fluororesin particles is preferably 0.5 μm or less, particularly 0.3 μm or less.
[0026] The fluororesin constituting the fluororesin particles can be a high molecular weight PTFE that does not exhibit melt fluidity even at or above the melting point, in addition to the above-mentioned heat-meltable perfluororesin. The high molecular weight PTFE particles also act as a filler, improving the durability of the coating film and improving the releasability. As such PTFE, an aqueous PTFE dispersion obtained by emulsion polymerization is preferably used.
[0027] The fluororesin particles are desirably contained in an amount of 10% by weight or more, preferably 20 to 60% by weight, more preferably 30 to 50% by weight of the entire base resin (total weight of rubber and fluororesin particles) contained in the coating composition. If the content of the fluororesin particles is less than the above range, the above-mentioned effects due to the inclusion of the fluororesin particles cannot be fully obtained, while if the amount of the fluororesin particles is more than the above range, the coating film may become too soft compared to when it is within the above range, resulting in a risk of reduced abrasion resistance.
[0028] [Silane coupling agents] In the coating composition of the present invention, it is preferable to contain a silane coupling agent in order to improve the adhesion between the coating film and the plastic substrate or rubber substrate. In particular, when silicone rubber is used, the incorporation of a silane coupling agent further improves the adhesion of the coating film to the rubber substrate. Silane coupling agents that can be used in the coating composition of the present invention may be conventionally known, and are not limited thereto. Examples of such agents include amino group-containing silane coupling agents such as γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, and N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane; glycidyl group-containing silane coupling agents such as γ-glycidoxypropyltrimethoxysilane and γ-glycidoxypropylmethyldimethoxysilane; and γ-mercaptopropyltrimethoxysilane. Examples of the silane coupling agents include mercapto group-containing silane coupling agents such as vinyltriethoxysilane, vinyltrimethoxysilane, vinyltris(methoxyethoxy)silane, etc.; vinyl group-containing silane coupling agents such as vinyltriethoxysilane, vinyltris(methoxyethoxy)silane, etc.; (meth)acryloyl group-containing silane coupling agents such as γ-(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, γ-(meth)acryloyloxypropyldimethoxymethylsilane, etc.; and isocyanate group-containing silane coupling agents such as γ-isocyanatepropyltriethoxysilane, γ-isocyanatepropyltrimethoxysilane, etc.
[0029] The silane coupling agent is preferably blended in an amount of 0.5 to 3.0% by weight, particularly 0.8 to 2.5% by weight, based on the total solid content of the base resin in the coating composition (rubber, or the total of rubber and fluororesin particles when fluororesin particles are contained). If the amount of the silane coupling agent is less than the above range, the above-mentioned effects obtained by blending the silane coupling agent are not sufficiently obtained, while if the amount of the silane coupling agent is more than the above range, the non-adhesiveness (releasability) of the coating film may be impaired compared to when it is within the above range.
[0030] [Preparation of coating composition] As described above, the coating composition of the present invention is preferably a water-based coating composition, and the preparation of such a water-based coating composition can be, for example, by the following preparation method, although it is not limited thereto. When the coating composition of the present invention is prepared as a water-based coating composition, it can be prepared by mixing an aqueous dispersion of rubber (latex) or a solution of a rubber precursor prepared by a conventional method with oil (preferably dispersed in a liquid medium in advance), an aqueous dispersion of fluororesin particles or a mixture thereof (for example, an existing water-based fluororesin coating material) optionally contained, a silane coupling agent, or other additives described later.
[0031] The aqueous dispersion of rubber can be prepared by a conventional method, including but not limited to emulsion polymerization, suspension polymerization, a method using an emulsifying device such as a high-speed homogenizer, an inversion emulsification method, a phase inversion temperature emulsification method, an emulsification method using a surfactant, or the like. In the aqueous dispersion of rubber, rubber particles having an average particle size of 0.01 to 0.5 μm are preferably dispersed in the aqueous dispersion at 10 to 70% by weight. The aqueous dispersion of fluororesin particles can be prepared by uniformly and stably dispersing the fluororesin particles in an aqueous solution using a surfactant or the like, or by subjecting the fluororesin to aqueous emulsion polymerization using a surfactant and an initiator, and optionally a chain transfer agent or the like. In the fluororesin aqueous dispersion, it is preferable that fluororesin particles having an average particle size of 0.01 to 180 μm are dispersed in the aqueous dispersion at 10 to 70% by weight.
[0032] In the coating composition of the present invention, the above-mentioned aqueous dispersion of rubber and the aqueous dispersion of fluororesin contained as necessary can be used as is, but fillers and various additives used in ordinary coatings can also be added depending on the desired properties, such as dispersibility, electrical conductivity, foam prevention, and improved abrasion resistance. For example, surfactants (e.g., Leocol (registered trademark) manufactured by Lion Corporation, Polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ether-based nonionic surfactants such as TRITON (registered trademark), TERGITOL (registered trademark) series, and Kao Corporation's Emulgen (registered trademark); sulfosuccinates, alkyl ether sulfonates, mono-long-chain alkyl sulfate-based anionic surfactants such as Lion Corporation's Repearl (registered trademark), Kao Corporation's Emal (registered trademark), and Pelex (registered trademark); polycarboxylates, acrylate-based polymer surfactants, such as Lion Corporation's Leoar (registered trademark) and Dow Chemical Company's OROTAN (registered trademark); film-forming agents (for example, polymer-based film-forming agents such as polyamide, polyamideimide, acrylic, and acetate, higher alcohols, ethers, and polymer surfactants having a film-forming effect), thickeners (water-soluble celluloses, solvent dispersion thickeners, sodium alginate, casein, sodium caseinate, xanthan gum, polyacrylic acid, and acrylic acid esters) can also be added.
[0033] <Water-based paint composition> The aqueous coating composition of the present invention can be prepared by blending oil in an amount of 1 to 35% by weight, preferably 2 to 20% by weight, more preferably 5 to 10% by weight, relative to the solids content of the base resin in the coating composition (rubber, or the total of rubber and fluororesin particles when fluororesin particles are contained), with the aqueous dispersion of rubber, aqueous dispersion of fluororesin, or an aqueous composition thereof prepared by the above-mentioned method, and mixing and stirring. In the coating composition of the present invention, it is important that the oil is finely dispersed in the coating composition in order to form a coating film that is free of defects such as bumps and has excellent smoothness.Finely dispersed oil also remains dispersed in the coating film that is formed, and is important for the oil to seep out onto the coating film surface over a long period of time, thereby exhibiting high non-stick properties (mold releasability). From this viewpoint, it is preferable that the oil is dispersed in the coating composition with an average particle size of 50 μm or less, particularly 20 μm or less. The oil can be used alone, but it is preferable to use a surfactant in combination with the oil to finely disperse the oil.
[0034] As the surfactant used to improve the dispersibility of the oil, a conventionally known surfactant can be used. In the present invention, when a fluoro oil is used, it is possible to highly disperse the fluoro oil by using a surfactant having excellent affinity with the fluoro oil, and therefore it is desirable to use a fluorosurfactant having a fluorocarbon structure as the hydrophobic group. Specific examples of fluorine-based surfactants include the Capstone (registered trademark) series (manufactured by Chemours Inc.), the Megafac series (manufactured by DIC Corporation), and Futergent (manufactured by Neos Corporation). In the present invention, when silicone oil is used, it is preferable to use the silicone surfactant that has silicone structure as hydrophobic group, because the surfactant that has excellent affinity with silicone oil can highly disperse silicone oil.In addition, when silicone oil is used, when silane coupling agent is mixed, it is preferable to add it immediately before painting, in order to promote the crosslinking of silicone. Examples of silicone surfactants include organopolysiloxanes modified with hydrophilic groups, such as polyoxyethylene (POE)-modified organopolysiloxanes, polyoxyethylene-polyoxypropylene (POE-POP)-modified organopolysiloxanes, POE sorbitan-modified organopolysiloxanes, and POE glyceryl-modified organopolysiloxanes. Specific examples include DBE-712, DBE-821 (manufactured by AZMAX Co., Ltd.), KF-6015, KF-6016, KF-6017, KF-6028 (manufactured by Shin-Etsu Chemical Co., Ltd.), ABIL-EM97 (manufactured by Goldschmidt), Polyflow KL-100, Polyflow KL-401, Polyflow KL-402, Polyflow KL-700 (manufactured by Kyoeisha Chemical Co., Ltd.), etc. The surfactant is preferably blended in an amount of 1 to 200 parts by weight, and more preferably 5 to 100 parts by weight, per 100 parts by weight of the oil.
[0035] Furthermore, when using the above-mentioned surfactants, the oil can be diluted with a fluorine-based solvent or other solvent to reduce its viscosity. This allows the oil to be more finely dispersed when it is mixed and stirred with water, an aqueous rubber dispersion, or a mixture of an aqueous fluororesin dispersion. Examples of fluorine-based solvents that can be used for diluting oil include fluorine-based solvents such as hydrofluorocarbons (HFCs), perfluorocarbons (PFCs), hydrochlorofluorocarbons (HCFCs), chlorofluorocarbons (CFCs), hydrofluoroolefins (HFOs), hydrochlorofluoroolefins (HCFOs), and hydrofluoroethers (HFEs). The solvent is desirably mixed in an amount of 100 to 500 parts by weight per 100 parts by weight of the oil.
[0036] In order to disperse the oil finely, it is also preferable to use the surfactant and then carry out ultrasonic dispersion or dispersion at a high shear rate. For these dispersions, a commonly used ultrasonic disperser, a stirrer, or various (high pressure, high speed, ultrasonic, etc.) homogenizers can be used. By using these, the oil can be finely dispersed without being diluted with a solvent, which is preferable from the viewpoint of simplifying the process and reducing the cost associated with the use of a fluorine-based solvent. Of course, it is also possible to dilute the oil with a solvent before carrying out the above dispersion, which is expected to result in finer dispersion.
[0037] <Solvent-based coating composition> When preparing a solvent-based coating composition, a liquid rubber, a rubber solvent dispersion, a fluororesin solution, or a fluororesin solvent dispersion is prepared, and an oil, preferably the above-mentioned oil dispersion, is blended therewith in an amount of 1 to 35% by weight of the base resin solids in the coating composition (the total weight of the rubber and optionally the fluororesin particles contained in the coating composition), and the mixture is stirred and mixed to prepare the composition.
[0038] <Powder coating composition> When preparing a powder coating composition, oil, preferably the above-mentioned oil dispersion, is blended into the aqueous dispersion of rubber or aqueous dispersion of fluororesin prepared by the above method in an amount of 1 to 35% by weight of the resin solid content in the coating composition (the total weight of the rubber and fluororesin contained in the coating composition as necessary), and stirred to coagulate the rubber, fluororesin, and oil. By stirring at a stirring speed of 100 to 500 rpm for 10 to 60 minutes, aggregated granules with an average particle size of 1 to 200 μm are granulated, and then separated, washed, and dried, the oil is filled into the voids of the primary particles of the rubber and fluororesin, and a rubber-fluororesin / oil composite powder in which the oil is uniformly present in the powder can be prepared. If necessary, large coarse particles with a particle size of 200 μm or more generated during the aggregation or granulation process can be crushed to make them finer. In order to chemically aggregate the primary rubber / fluororesin particles, it is preferable to mix in an electrolyte such as HCl, H2SO4, HNO3, H3PO4, Na2SO4, MgCl2, CaCl2, HCOONa, CH3COOK, (NH4)2CO3, etc. Furthermore, if necessary, it is preferable to add an organic solvent that is incompatible with water (preferably a fluorine-based solvent) to uniformly granulate the aggregated particles.
[0039] <Other> Various organic and inorganic fillers can be added to the coating composition of the present invention depending on the desired properties. Examples of organic fillers include engineering plastics such as polyarylene sulfide, polyether ether ketone, polyamide, and polyimide. Examples of inorganic fillers include metal powder, metal oxides (aluminum oxide, zinc oxide, tin oxide, titanium oxide, etc.), glass, ceramics, silicon carbide, silicon oxide, calcium fluoride, carbon black, graphite, mica, and barium sulfate. Fillers of various shapes, such as particulate, fibrous, and flake shapes, can be used. In addition to the above, pigments and various additives that have traditionally been used in paints can be blended depending on the desired characteristics, such as electrical conductivity, foam prevention, and improved abrasion resistance. The use of these fillers not only gives various properties to the coating film, but also imparts fine irregularities to the surface of the mating material (molded product) when the coating composition of the present invention is coated onto a molding mold, thereby suppressing gloss.
[0040] As described above, the abrasion resistance of the coating composition of the present invention is improved by the presence of oil, but the abrasion resistance can be further improved by blending a filler. Particularly suitable fillers include, but are not limited to, silicon carbide (SiC), silica, and polyimide (PI). The amount of filler to be blended depends on the type of filler used and cannot be generally determined, but is preferably in the range of 0.1 to 10% by weight based on the paint solids content of the paint composition (total solids remaining as the coating film excluding oil, i.e., the total amount of rubber, fluororesin, and filler). If the amount of filler to be blended is less than the above range, the improvement in abrasion resistance due to the blending of the filler is poor, while if the amount is more than the above range, the releasability may be reduced compared to when it is in the above range. When the coating composition is a liquid coating such as a water-based coating, the filler is preferably used by dispersing it in a liquid medium such as water.
[0041] (Coating method) The coating composition of the present invention can be applied by a conventional coating method such as spray coating or dip coating. After coating, the applied coating composition is heated to the crosslinking temperature of the rubber to form a coating film. As described above, in the coating composition of the present invention, since the crosslinking temperature of the rubber is low at 120 to 200° C., even if the coating composition is directly applied to a plastic or rubber substrate and then heat-treated, a uniform coating film can be formed without damaging the substrate. The heating conditions (baking conditions) of the coating composition of the present invention vary depending on the composition and form of the coating composition, the coating amount, the desired crosslinking temperature, etc., and cannot be generally specified, but it is preferable to heat for 5 to 120 minutes at a temperature equal to or higher than the crosslinking temperature of the rubber used. In addition, by carrying out the heat treatment multiple times, it is possible to promote crosslinking and improve abrasion resistance. Furthermore, since the coating composition of the present invention has excellent adhesion to plastic and rubber substrates, it can be directly applied to the surface of the substrate without the need for a primer layer or surface treatment of the substrate.
[0042] (Plastic or rubber substrate) As described above, the coating composition of the present invention is capable of forming a coating film at low temperatures and is therefore applicable to substrates with poor heat resistance, and is particularly suitable for use on plastic substrates or rubber substrates. Specifically, the coating composition can be used on resins or resin compositions such as thermoplastic resins, thermosetting resins, photocurable resins, and electron beam curable resins, as well as conventionally known polymeric materials such as rubber and thermoplastic elastomers. A coating film made from the coating composition of the present invention has the property of being able to follow the expansion and contraction of the substrate, and therefore can be suitably used for elastic rubber substrates among the above substrates.
[0043] Examples of thermoplastic resins that can be used to form the substrate include, but are not limited to, olefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, acrylic resins such as polymethyl methacrylate, polycarbonate, polyimide, and polyamide resins. Examples of the thermosetting resin include, but are not limited to, phenol resin, epoxy resin, melamine resin, unsaturated polyester resin, silicone resin, and the like. Examples of photocurable resins include, but are not limited to, acrylic resins made of mono- or difunctional monomers, polyfunctional monomers, polyfunctional oligomers, or polyfunctional polymers having one or more (meth)acryloyl groups in one molecule, and examples of electron beam curable resins include, but are not limited to, epoxy acrylate, polyester acrylate, polyurethane acrylate, epoxy methacrylate, polyester methacrylate, polyurethane methacrylate, etc.
[0044] Examples of rubbers that can be used to form the base material include saturated polyolefin-based rubbers such as ethylene-propylene copolymers, ethylene-α-olefin copolymers, propylene-α-olefin copolymers, chlorinated polyethylene, and chlorosulfonated polyethylene; α-olefin-diene copolymer-based rubbers such as ethylene-propylene-diene copolymers, α-olefin-diene copolymers, ethylene-diene copolymers, propylene-diene copolymers, and halogenated and hydrogenated versions of these; diene polymer-based rubbers such as isoprene rubber, butadiene rubber, and halogenated and hydrogenated versions of these; silicone-based rubbers such as methyl silicone rubber, vinyl-methyl silicone rubber, and phenyl-methyl silicone rubber; fluorinated silicone rubber; and bifluorinated silicone rubber. Examples of such rubbers include fluororubbers such as ethylene-tetrafluoroethylene-propylene rubber, tetrafluoroethylene-perfluoromethylvinyl ether rubber, etc.; styrene-diene copolymer rubbers such as styrene-butadiene copolymer, styrene-isoprene copolymer, etc.; butyl rubber, its halides, hydrogenated products, etc.; chloroprene rubbers such as chloroprene, its halides, hydrogenated products, etc.; epichlorohydrin rubber, epichlorohydrin-ethylene oxide rubber, etc.; urethane rubbers such as polyether urethane rubber, polyester urethane rubber, etc.; acrylonitrile-butadiene rubber, its halides, hydrogenated products, etc.;
[0045] Examples of thermoplastic elastomers include styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-ethylene-butadiene-styrene block copolymers, styrene-isoprene-butadiene-styrene block copolymers, styrene-ethylene-propylene-styrene block copolymers, halogenated and hydrogenated polystyrene-based thermoplastic elastomers, blends of olefin resins and olefin rubber, blends of olefin resins and olefin-diene copolymers, halogenated and hydrogenated polyolefin-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, and polyester-based thermoplastic elastomers.
[0046] In addition, depending on the material used, a crosslinking agent, a polymerization initiator, a filler, a pigment, an ultraviolet absorber, an antiaging agent, a foaming agent, a defoaming agent, an antioxidant, and the like can be added to the above-mentioned polymer material constituting the base material by a conventionally known recipe. The coating film formed by the coating composition of the present invention has excellent durability and can maintain non-stickiness (mold releasability) for a long period of time, and is therefore particularly suitable for use as a top coat to be applied to the surfaces of rubber products, such as bladders for tire manufacturing, made of a rubber composition, and plastic molding dies.
[0047] (Paint film) The thickness of the coating film can be appropriately selected depending on the use of the substrate and the application part, but when used to improve the releasability of the bladder or plastic molding die as described above, it is preferable to apply so that the film thickness after heat treatment is 5 μm or more, particularly 5 to 300 μm. If the film thickness is thinner than the above range, a continuous coating film cannot be formed compared to when it is within the above range, and there is a risk of coating film defects occurring, and there is a risk of early loss of coating film performance (non-adhesiveness (releasability), slipperiness) due to wear. On the other hand, even if the film thickness is thicker than the above range, further improvement in coating film performance such as releasability cannot be expected, and it becomes less economical.
[0048] The coating film formed on the surface of a substrate using the coating composition of the present invention contains 1 to 35% by weight of oil and has high non-adhesive properties (releasability) with an n-hexadecane contact angle of 50 degrees or more, preferably 60 degrees or more. EXAMPLES
[0049] (Measurement of physical properties) [Average diameter of oil particles in paint] The obtained coating composition was dropped onto a glass slide (micro slide glass 76x26mm, 1-1.2mmt, Matsunami) using a dropper, then placed on an aluminum substrate (50mm x 100mm, 1mm thick), and observed under an optical microscope (Hirox Co., Ltd., KH-1300) in reflection mode, and the oil particles were observed using photographs at 2000-2500 magnifications. The average value of n=20 samples was calculated and used as the average particle size. When the average particle size was 50μm or less, it was marked with "◎".
[0050] [Creating test pieces] The following two types of substrates were used: -Butyl rubber (IIR) sheet (size: 100mm x 50mm x 1mmt (Paltec Co., Ltd.) Silicone rubber sheet (size: 100mm x 50mm x 1mmt (Paltec Co., Ltd.) Aluminum test piece (size: 100mm x 50mm x 1mmt, JIS A5052 compliant)
[0051] [Substrate surface treatment] The rubber substrates (butyl rubber sheet and silicone rubber sheet) were used as they were after the surfaces had been air-blowed. The aluminum substrate was degreased with isopropyl alcohol, and the surface was roughened by shot blasting with #60 alumina (Showa Blaster, Showa Denko K.K.) using a sandblaster (Pneumatic Blaster SGF-4(A)S-E566, manufactured by Fuji Manufacturing Co., Ltd.), and then wiped with isopropyl alcohol.
[0052] [Painting and coating] Each of the above substrates was sprayed with an air spray gun (ANEST IWATA Corp. W-88-10E2 φ1mm nozzle (manual gun)) at an air pressure of 2.5-3.0kgf / cm. 2 The coating composition thus obtained was sprayed onto the substrate to carry out coating, so that the weight of the liquid applied was about 0.65 g (0.60 to 0.70 g) per substrate, to prepare test pieces. The baking conditions are as follows: After drying by heating at 60°C for 10 minutes, it was transferred to another oven and heated at 120°C for 10 minutes, then transferred to another oven and heated for crosslinking at 180°C for 10 minutes, and then transferred to another oven. The secondary crosslinking treatment was carried out by heating at 120°C for 60 minutes.
[0053] [Releasability evaluation (n-hexadecane contact angle)] Using the test pieces obtained by the above method, the contact angle of n-hexadecane (droplet size: approximately 2 μL) was measured using a fully automatic contact angle meter (Kyowa Interface Science Co., Ltd. DM-701) in a measurement environment of 25°C and 60% RH.
[0054] [Adhesion evaluation (cross-cut test)] The coating surface of the test piece obtained by the above method was subjected to the following cross-cut test in accordance with JIS K 5600.5.6. (1) Using a cutter knife, make 11 cuts reaching down to the base material on the test surface to create 100 grids. A cutter guide was used, and the cuts were spaced 1 mm apart. (2) Firmly press Scotch tape (registered trademark) onto the grid area, then quickly peel off one end of the tape at a 45° angle, and evaluate the condition of the grid area by comparing it with the standard diagram. The evaluation results were expressed as the number of peeled squares (per 100).
[0055] [Extension test] The obtained coating composition was applied to one side of a 100 mm long, 50 mm wide, 1 mm thick butyl rubber substrate (manufactured by Partec Co., Ltd.), and heat crosslinked at 180°C for 10 minutes and at 120°C for 60 minutes to form a coating film with a thickness of 50 μm. A dumbbell-shaped test piece (based on ASTM D-2116) was cut out from the coated substrate, and a stretching test was performed using a constant stretching repeated fatigue tester (MYSS Tester, H9537 / H9606, manufactured by Mize Testing Co., Ltd.) under the conditions of a measurement temperature of 200°C, a deformation stroke of 11 mm (50% stretched), a stretching speed and return speed of 11 mm / min, and a number of stretches of 200 times. After the test, the condition of the coating film was checked, and if no cracks or peeling occurred, it was judged to have passed.
[0056] [Raw rubber vulcanization test (hot press)] The test piece (painted rubber substrate) obtained by the above method was placed in a mold, and a sheet of raw rubber (uncrosslinked butyl rubber) about 3 mm thick cut to about 3 cm x 10 cm was placed on top of it, and vulcanization was performed by heating and pressurizing it at 180 ° C x 2 MPa x 10 minutes using a compression molding machine (hot press WFA-37, manufactured by Shinto Metal Industries, cylinder diameter: 152 mm). After vulcanization was completed, the vulcanized rubber layer was peeled off from the substrate to check the coating film condition. If the substrate could be easily removed from the vulcanized rubber and the coating film did not peel off from the substrate, it was evaluated as "◯", if the rubber substrate could be removed from the vulcanized rubber but some dirt remained, it was evaluated as "△", and if the rubber substrate did not peel off from the vulcanized rubber or the coating film peeled off from the rubber substrate, it was evaluated as "X".
[0057] Example 1 15.39g of PFPE (Krytox XHT1000 manufactured by Chemours, decomposition temperature 426°C) as fluorine oil and 30.78g of fluorine-based surfactant (Capstone FS-31 manufactured by Chemours) were placed in a 1-liter stainless steel beaker, and ultrasonic dispersion treatment was performed for 10 minutes using an ultrasonic generator (Ultrasonic MINIWELDER HS3-4 manufactured by Ultrasonic Industries Co., Ltd.), and then 1.94g of pure water and 189.94g of FEP aqueous dispersion (Teflon (registered trademark) FEP 120-JR (FEP resin solid content 54.5% by weight) manufactured by Mitsui-Chemours Fluoro Products Co., Ltd.) as fluorine resin particles were added, and the mixture was stirred at 200 rpm for 10 minutes using a downflow type propeller-type 4-blade agitator, and then hydrogenated acrylonitrile butadiene rubber dispersion (Zetpol (registered trademark) 2230LX (HNBR solid content 40.6% by weight) manufactured by Zeon Corporation) were added. 250.63 g was added and stirred at 150 rpm for another 5 minutes. 9.02 g of a 10 wt % aqueous methylcellulose solution and 2.3 g of a silane coupling agent (KBM-603, manufactured by Shin-Etsu Chemical Co., Ltd.) were added thereto and stirred at 250 rpm for 15 minutes to obtain a coating composition.
[0058] (Examples 2 and 3) A coating composition was prepared in the same manner as in Example 1, except that the content of the fluorinated oil was adjusted to the ratio shown in Table 1.
[0059] Example 4 A coating composition was prepared in the same content ratio as in Example 1, except that a PFA aqueous dispersion (Teflon (registered trademark) PFA 334-JR (PFA resin solid content 60% by weight) manufactured by Mitsui-Chemours Fluoroproducts Co., Ltd.) was used as the fluororesin particles.
[0060] Example 5 A coating composition was prepared in the same manner as in Example 4, except that the content of the fluorinated oil was adjusted to the ratio shown in Table 1.
[0061] Example 6 A coating composition was prepared in the same content ratio as in Example 1, except that an aqueous PTFE dispersion (Teflon (registered trademark) PTFE 34-JR (PTFE resin solid content 58% by weight) manufactured by Mitsui-Chemours Fluoroproducts Co., Ltd.) was used as the fluororesin particles.
[0062] Example 7 A coating composition was prepared in the same manner as in Example 2, except that no silane coupling agent was used.
[0063] Example 8 6.15g of PFPE (Krytox XHT-1000, manufactured by Chemours Co., Ltd.) was added to 12.3g of fluorosurfactant (Capstone FS-31, manufactured by Chemours Co., Ltd.) as fluorine oil, and ultrasonic dispersion treatment was performed for 10 minutes. This mixed composition liquid was added to a mixture of 45.78g of pure water and 182.97g of FEP aqueous dispersion liquid (Teflon (registered trademark) FEP 120-JR (FEP resin solid content 54.5% by weight, manufactured by Mitsui Chemours Fluoro Products) and stirred at 200 rpm for 10 minutes using a downflow type propeller type four-blade mixer. 241.44g of silicone rubber dispersion liquid (KM-2002-T (silicone rubber solid content 40% by weight, manufactured by Shin-Etsu Chemical Co., Ltd.) was added and stirred at 200 rpm for another 5 minutes. Next, 4.34 g of a 10 wt % aqueous methylcellulose solution and 7.01 g of a black pigment (CB 853-4297, manufactured by Chemours Inc.) were added to the above mixture and stirred at 250 rpm for 15 minutes to obtain 500 g of a coating composition.
[0064] (Examples 9 and 10) A coating composition was prepared in the same manner as in Example 7, except that the blending ratio of the silicone rubber and the fluororesin particles was set to the ratio shown in Table 1.
[0065] Comparative Example 1 A coating composition was prepared in the same content ratio as in Example 1, except that no fluorinated oil was used.
[0066] Comparative Example 2 A coating composition was prepared in the same manner as in Comparative Example 1, without using fluorinated oil and fluorinated resin particles, and in the composition ratio shown in Table 1.
[0067] Comparative Example 3 A coating composition was prepared in the same manner as in Example 10 using the composition ratio shown in Table 1, without using fluorinated oil.
[0068] [Table 1]
Claims
1. A coating composition comprising rubber, oil which is liquid at 25°C, and fluororesin particles, the rubber being contained in an amount of 50% or more of the entire base resin, and the oil being dispersed with an average particle size of 50 μm or less.
2. 2. The coating composition of claim 1, which further comprises a silane coupling agent.
3. 3. The coating composition according to claim 1 or 2, wherein the oil is contained in an amount of 1 to 35% by weight of the amount (solid content) of the rubber in the coating composition or the total amount (solid content) of the rubber and the fluororesin particles.
4. The coating composition according to any one of claims 1 to 3, wherein the rubber is hydrogenated acrylonitrile butadiene rubber or silicone rubber.
5. The coating composition according to any one of claims 1 to 4, wherein the oil is a fluorine oil or a silicone oil.
6. 6. The coating composition according to claim 1, wherein the fluororesin particles are made of a melt processable fluororesin.
7. The coating composition according to any one of claims 1 to 6, wherein the fluororesin particles are made of PFA or FEP.
8. 8. A rubber or plastic substrate having a coating film on its surface, the coating film comprising the coating composition according to claim 1, and an oil dispersed within the coating film.
9. 9. The rubber or plastic substrate according to claim 8, wherein the coating has a contact angle with n-hexadecane of 50 degrees or more.
Citation Information
Patent Citations
Production of color filter
JP1987055604A
Fluororubber coating composition and method for modifying substrate surface
JP1994264021A
Mold release lubricant for molding tire
JP2000158454A
Heat insulation coating
JP2017031322A
Fluororesin coating composition
JP2018090772A